Targeted Cancer Therapy: The Next Generation of Cancer Treatment - A. Baudino, Troy (Current Drug Discovery Technologies, 2015)
Cancer is one of the leading causes of death in the United States along with heart disease. The hallmark of cancer treatment has been conventional chemotherapy. Chemotherapeutic drugs are designed to target not only rapidly dividing cells, such as cancer cells, but also certain normal cells, such as intestinal epithelium. Over the past several years, a new generation of cancer treatment has come to the forefront, i.e, targeted cancer therapies. Like conventional chemotherapy, targeted cancer therapies use pharmacological agents that inhibit growth, increase cell death and restrict the spread of cancer. As the name suggests, targeted therapies interfere with specific proteins involved in tumorigenesis. Rather than using broad base cancer treatments, focusing on specific molecular changes which are unique to a particular cancer, targeted cancer therapies may be more therapeutically beneficial for many cancer types, including lung, colorectal, breast, lymphoma and leukemia. Moreover, recent advances have made it possible to analyze and tailor treatments to an individual patient’s tumor. There are three main types of targeted cancer therapies; 1) monoclonal antibodies, 2) small molecule inhibitors and 3) immunotoxins. This review will discuss these three classes of targeted therapies in detail, as well as the biology behind targeted cancer therapies.
Keywords: chemotherapy